The Effect of Yoga and Pelvic Floor Muscle Exercise on Sexual Function and Sexual Selfesteem of Reproductive-age Women: A Randomized Clinical Trial - Narges Tabatabaie; Fereshteh Rasti Borujeni; Zeinab Tavakol; Hadi Raeisi Shahraki (Shiraz University of Medical Sciences, 2024)
Background: Sexual function is a part of sexual health which is an important aspect of the quality of life. Physical activity is one of the healthiest activities that can effectively reduce the risk of sexual disorders. Therefore, this study was conducted with the aim of evaluating the effect of yoga and pelvic floor muscle exercises on the sexual function and sexual self-esteem of reproductive-age women.Methods: This randomized clinical trial study was conducted from September to December 2023 on 46 women of reproductive age working in the Shahrekord University of Medical Sciences and its affiliated health centers. Multi-stage cluster sampling was used to select the subjects; later, they were randomly divided into two intervention groups A (N=21) and B (N=25). Participants in intervention groups A and B performed pelvic floor muscle exercises at home using an educational pamphlet 3 times a week for 6 weeks, with 3 times a day repetition. In addition, women in the intervention group A participated in a yoga training program for 2 sessions per week for 6 weeks. Data collection tools included a demographic information form, the Female Sexual Function Index, and Sexual Self-Esteem Inventory for women. Questionnaires were completed by both groups before, immediately, and one month after the intervention. The data were analyzed using the chi-square test, fisher's exact test, independent two-sample t-test, repeated measures test, and analysis of covariance in SPSS software version 16. A significance level of less than 0.05 was considered.Results: The results showed no statistically significant difference between the two groups in sexual function (P=0.21) and sexual self-esteem (P=0.22) scores before the intervention. Also, the results showed no statistically significant difference between the two groups in terms of sexual function (P=0.35) and sexual self-esteem (P=0.59) scores one month after the intervention. However, the mean score of the sexual function index immediately after intervention showed a statistically significant difference between the intervention groups A (31.43±3.76) and B (29.41±2.38) (P<0.001). The mean score of the sexual self-esteem immediately after the intervention showed a statistically significant difference between the intervention groups A (181.19±19.90) and B (171.32±15.02) (P<0.001).Conclusion: Adding yoga exercises to pelvic floor muscle exercises can improve the sexual function and sexual self-esteem of women at their reproductive age.Trial Registration Number: IRCT20100524004015N1.